SITUASI KEBAHASAAN MASYARAKAT MULTILINGUAL DI KAWASAN CIMUNCANG KOTA BANDUNG : Kajian Sosiolinguistik - Disa Nur Agnia Salsabilla, - (2023)
The situation and conditions of a multilingual society are prone to potential linguistic conflicts, especially conflicts caused by errors in the form of language code selection which are often caused by sociocultural factors and the situational context of the community. The problems include: (1) a portrait of the language situation in the speech community in Cimuncang Area, Bandung City (2) the form of language code variation in the language selection of the community, and (3) sociocultural factors that determine language selection in various speech events of the community. This research uses a sociolinguistic approach that utilizes qualitative descriptive methods. The source of data in this study was obtained from a multilingual community. While the data of this research is oral speech in the sociocultural context and situational context in Cimuncang Area, Bandung City. The research instrument was carried out by filling in data cards to transcribe the previously recorded speech, identifying, classifying, and finally presenting the results of data analysis and drawing conclusions. The analysis process was conducted using reflective-introspective methods with formal and informal presentation methods. With this series of research analysis, the potential for linguistic conflicts caused by misunderstanding the meaning of words in language selection can be minimized and controlled.